The potential of sclerocarya birrea caffra nut meal as a dietary protein source in broiler and layer cortunix cortunix japonicum - Mazizi, Bulelani Elvis (My University, 2020)
Despite its high crude protein (CP) content, Marula nut meal’s (MNM) potential as a dietary protein source has not been evaluated in quail. Following determination of the nutrient composition of hexane-extracted MNM and comparing it with soyabean meal (SBM), its suitability as a substitute in broiler and pullet quail feeds was evaluated by determining its effects on productivity, health and product quality. In the broiler study, 200 nine-day old broiler Japanese quail chicks, in a simple randomised interventional study, were allocated to five grower diets wherein MNM substituted SBM (CP basis) at 0%, 25%, 50%, 75% and 100% and fed for 4 weeks. The quail were then transferred to similarly constituted finisher diets and fed for 2 weeks. Weekly body weight and daily feed intake (FI) were measured. Bodyweight gain (BWG), average daily gain (ADG) and feed conversion ratio (FCR) were computed. At slaughter, blood was collected and carcasses eviscerated. Viscera macro-morphometry, biomarkers of liver and kidney function, carcass traits and the meat’s pHi and pHu, colour, thawing and cooking loss (TL and CL), tenderness, proximate and fatty acid composition were determined. In the pullet study, sixty 5-week old Japanese quail hens were, in a simple randomised design, allocated to five pullet diets wherein MNM substituted SBM (CP basis) at 0%, 25%, 50%, 75% and 100% and fed for 8 weeks. Egg production and quality, growth performance and feed utilisation efficiency, viscera macro-morphometry, plasma uric acid, calcium and phosphorus concentration were determined. Proximate, fibre (aNDF, ADF and ADL), phosphorus, gross energy (GE), amino acid and TMUFA content of MNM was higher (P <0.05) than that of SBM. Dietary MNM had no effect (P >0.05) on terminal body mass, BMG, ADG, FI, FCR and carcass mass of broiler and pullet quail. Meat from broiler quail fed diet 1 had the lowest (P <0.05) pHi and pHu and was lighter and less red (P <0.01) compared to that from counterparts fed diet 5. MNM had no effect (P >0.05) on TL, CL and tenderness of the meat. The meat’s CP and fat content decreased with increasing dietary MNM but ash increased (P <0.05). At 50 to 100% inclusion level dietary MNM increased (P<0.05) the oleic acid (OA) content of the meat. Liver and kidney function of broiler quail was not affected (P >0.05) by MNM. Pullet hens fed diets 3 to 5 commenced laying at 9-weeks of age. Counterparts fed diets 1 and 2 commenced at 10-weeks. Percent lay of hens fed diets 3 to 5 was similar at 9-weeks of age. At v 10-weeks of age 50% of the hens fed diet 3 were laying. Their counterparts fed diet 5 were at 16.67%. The highest percentage of laying hens was at 13-weeks of age: hens fed diet 2 and 4 at 91.66% and those fed diets 1, 3 and 5 at 83.33%. The number of eggs per hen per week was similar (P >0.05) across the dietary treatments at 9-weeks of age. At 10-weeks of age hens fed diet 4 had a higher (P <0.05) number of eggs per hen compared to those fed diet 1. Hens fed diet 3 had a higher (P <0.05) number of eggs per hen compared to those fed diet 1. At 12 and 13 weeks of age, the number of eggs per hen per week was similar (P >0.05) across dietary treatments (P >0.05). The number of eggs per laying hen was similar at 9-weeks of age but at 10-weeks of age hens fed diet 5 had more eggs (P <0.0001) than from hens fed diets 1 to 4. At 11-weeks of age, the number of eggs per laying hen was lower (P <0.0001) for birds fed diet 1 compared to those fed diets 3 to 5. Dietary MNM had no effect on egg mass (EM) at 9, 10, 11 and 13-weeks of age. At 12-weeks of age hens fed diet 2 produced lighter (P >0.05) eggs compared to eggs from hens fed other diets. Dietary MNM had no effect (P >0.05) on egg shape index and shell thickness. At 9-weeks of age the yolk index of the eggs from hens fed diet 4 was lower (P >0.05) compared to that of eggs from birds fed diets 3. The albumen index of eggs from hens fed diet 4 was significantly lower (P <0.05) compared to that of eggs from hens fed diets 2 and 5. The yolk ratio of eggs from hens fed diets diet 3 was significantly higher (P <0.05) than that from counterparts fed diets 1 and 5. The yolks from eggs of birds fed diets 1 and 5 had lower (P <0.0001) fat content compared to that of eggs from birds fed diets 2 and 3. The egg yolk cholesterol content from birds fed diets 2 and 3 was higher (P <0.01) compared to that from hens fed diets 1, 4 and 5. Marula nut meal can substitute SBM in Japanese quail broiler and pullet diets without compromising growth performance, feed utilisation efficiency, bird health, meat quality and the external egg quality. It can be used to improve the redness and OA content of quail meat but caution must be taken in its use in quail pullet diets as it compromised internal egg quality.
A thesis submitted in fulfilment of the requirements for the degree of Doctor of Philosophy to the Faculty of Health Sciences, School of Physiology, University of the Witwatersrand, Johannesburg, 2020